2014
DOI: 10.1111/1365-2664.12243
|View full text |Cite
|
Sign up to set email alerts
|

Optimal planning for mitigating the impacts of roads on wildlife

Abstract: Summary1. Roads have a significant impact on wildlife world-wide. Two of the ways to mitigate the impact of roads are to improve connectivity and reduce mortality through fences and wildlife crossings. However, these are expensive actions that will have different effects in different places. Thus, deciding where and how to act in order to achieve the greatest return on investment is crucial. Currently, there are no quantitative approaches to prioritize different road mitigation options. 2. Here, we use a decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 54 publications
(113 reference statements)
0
47
0
2
Order By: Relevance
“…Two studies even cautioned that fencing was ineffective unless it was continually maintained and breaches in the fencing were repaired in a timely manner [111,113]. Furthermore, many studies suggested that road-related mortality could be further reduced when crossing structures were combined with fencing [97,114,115]. Moreover, one study on koalas (Phascolarctos cinereus) in Australia emphasized that selecting a single mitigation option was not economically viable [114].…”
Section: Survey Design and Mitigationmentioning
confidence: 99%
“…Two studies even cautioned that fencing was ineffective unless it was continually maintained and breaches in the fencing were repaired in a timely manner [111,113]. Furthermore, many studies suggested that road-related mortality could be further reduced when crossing structures were combined with fencing [97,114,115]. Moreover, one study on koalas (Phascolarctos cinereus) in Australia emphasized that selecting a single mitigation option was not economically viable [114].…”
Section: Survey Design and Mitigationmentioning
confidence: 99%
“…Over the last few decades, research and investment on mitigation measures to reduce wildlife mortality on roads have increased greatly (Jackson and Griffin 2000;Glista et al 2009;Polak et al 2014;Kociolek et al 2015;Ward et al 2015). In railways the efforts to increase wildlife safety have not been as considerable (van der Grift 1999;Dorsey et al 2015), and these efforts have been concentrated mostly on mitigating the impacts on existing railways, ignoring the expansion of the high-speed railway network (Dorsey et al 2015).…”
Section: How To Mitigate Wildlife Mortality In Railways?mentioning
confidence: 99%
“…Nonetheless, multispecies studies are still a rarity in the road ecology literature and, to our knowledge, so far none has focused on cost-effective mitigation planning for more than one species. Moreover, only a few studies incorporate cost-effectiveness at all into their mitigation planning (Putman et al 2004, Ascensão et al 2013, Polak et al 2014. Multispecies systematic planning is a common practice in other fields of conservation.…”
Section: Discussionmentioning
confidence: 99%
“…The aims are followed by a list of management actions, state variables and their dynamics, constraints and uncertainties, all of which are incorporated into a framework to try to find the best solution or a range of very good solutions to a conservation problem. Decision science incorporates budget constraints (Possingham et al 2001, Newburn et al 2005, Strange et al 2006, McCarthy and Possingham 2007, McDonaldMadden et al 2008, Tulloch et al 2011, prioritizes actions (Polak et al 2014), prepare for climate change (Hodgson et al 2009), dealing with uncertanties (Regan et al 2005) and facilitates resource allocation (Wilson et al 2006, Martin et al 2007, Game et al 2008). …”
Section: Decision Making In Conservationmentioning
confidence: 99%
See 1 more Smart Citation